Mitosis–meiosis and sperm–oocyte fate decisions are separable regulatory events - Morgan, Clinton T. (National Academy of Sciences, 2013)
Germ cell fate decisions are poorly understood, despite their central role in reproduction. One fundamental question has been whether germ cells are regulated to enter the meiotic cell cycle (i.e., mitosis–meiosis decision) and to be sperm or oocyte (i.e., sperm–oocyte decision) through one or two cell fate choices. If a single decision is used, a male-specific or female-specific meiotic entry would lead necessarily toward spermatogenesis or oogenesis, respectively. If two distinct decisions are used, meiotic entry should be separable from specification as sperm or oocyte. Here, we investigate the relationship of these two decisions with tools uniquely available in the nematode Caenorhabditis elegans. Specifically, we used a temperature-sensitive Notch allele to drive germ-line stem cells into the meiotic cell cycle, followed by chemical inhibition of the Ras/ERK pathway to reprogram the sperm–oocyte decision. We found that germ cells already in meiotic prophase can nonetheless be sexually transformed from a spermatogenic to an oogenic fate. This finding cleanly uncouples the mitosis–meiosis decision from the sperm–oocyte decision. In addition, we show that chemical reprogramming occurs in a germ-line region where germ cells normally transition from the mitotic to the meiotic cell cycle and that it dramatically changes the abundance of key sperm–oocyte fate regulators in meiotic germ cells. We conclude that the C. elegans mitosis–meiosis and sperm–oocyte decisions are separable regulatory events and suggest that this fundamental conclusion will hold true for germ cells throughout the animal kingdom.